2015
DOI: 10.15406/jdmdc.2015.02.00034
|View full text |Cite
|
Sign up to set email alerts
|

A Low Carbohydrate Diet Effective in the Treatment of Obese or Diabetic Patients with Chronic Kidney Disease

Abstract: Aim: Diet of Hope Institute specializes in the treatment of obesity, diabetes, hypertension, and metabolic syndrome. In 2011, a patient being treated at our clinic improved estimated glomerular filtration rate (eGFR) from 46 to 80. The patient was obese, hypertensive and diabetic. She lost 10% of her body weight and was able to stop her diabetic and blood pressure medications. This finding prompted the Institute to collect data regarding the frequency of kidney disease in the clinic's patient population and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Obesity increases the risk of prediabetes and cardiovascular disease. 6 All obese people should be screened for prediabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity increases the risk of prediabetes and cardiovascular disease. 6 All obese people should be screened for prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The diet has also been very successful in the treatment of patients with arteriosclerotic heart disease, chronic renal failure and diabetes and obesity. 5,6 Of 2,000 consecutive patients referred to the Diet of Hope program, 833 patients were found to be prediabetic based on an initial HbA1c result of 5.7 to 6.4%. Of those 833 patients, 692 patients were obese (83.1%) and the remaining 141 patients were overweight (16.9%).…”
Section: Methods and Materials Populationmentioning
confidence: 99%
“…Is the effect of SGLT2 inhibitors equivalent to that of carbohydrate restriction in diabetes treatment? A clinical report demonstrated that a low carbohydrate diet was effective in improving renal function in obese or diabetic patients with chronic kidney disease [22]. It has been shown that excessive intake of carbohydrates or simple carbohydrates was associated with obesity and chronic kidney disease [23][24][25].…”
Section: Sglt2 Inhibitors Versus Carbohydrate Restrictionmentioning
confidence: 99%